Environmental policy integration : greening sectoral policies in Europe - Lenschow, Andrea (London ; Sterling, VA : Earthscan Publications, 2002)
Integrating environmental policies into the policies of all other sectors is the core European environmental policy. But there has been no thorough investigation of the political process involved. This volume provides the first. It analyses the process of policy integration - the greening of public policy - across the relevant sectors and countries. It finds significant variation from sector to sector and from country to country, and analyses the reasons for this. (Surprisingly the UK, traditionally the 'dirty man' of Europe is far more actively engaged than environmental 'progressives' such as Germany.) It identifies the obstacles to integration and offers solutions for policy formulation, decision making and implementation at the relevant political levels.
Greening the European Union: an introduction / Andrea Lenschow -- Three conceptions of the integration principle in international environmental law / André Nolkaemper -- Efficient hardware and light green software: environmental policy integration in the UK / Andrew Jordan -- Environmental policy integration as a political principle: the German case and the implications of European policy / Edda Müller -- Environmental policy integration in Italy: is a green government enough? Some evidence from the Italian case / Rodolfo Lewanski -- Integrating European Union environmental and agricultural policy / Henry Buller -- Why does environmental policy integration fail? The case of environmental taxation for heavy goods vehicles / Christian Hey -- The sustainability of freight transport across the Alps: European Union policy in controversies on transit traffic / Volkmar Lauber -- European Union energy policy in a changing climate / Ute Collier -- Dynamics in a multilevel polity: greening the European Union regional and cohesion funds / Andrea Lenschow -- Conclusion: what are the bottlenecks and where are the opportunities for greening the European Union? / Andrea Lenschow.
Includes bibliographical references and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: Environmental policy -- European Union countries; Environnement -- Politique gouvernementale -- Pays de l'Union européenne.; SCIENCE -- Environmental Science (see also Chemistry -- Environmental); POLITICAL SCIENCE -- Public Policy -- Environmental Policy; Environmental policy; European Union countries; Milieubeleid; Beleidsvorming; Europese integratie